(untitled) (Communication & Society, 2009)
This research is based on a long term content analysis study on news coverage of water issues in Spanish press in a 45 year span, during 1960-2004, in the attempt to examine the way how modern concepts or topics have been added up as new frames to the deep-rooted water issues of long tradition in Spain or, simply, they have taken over the old ones. It is observed how different groups of stakeholders have contributed to bring forward agenda of new topics as well as new social actors in the news coverage of water issues in nationwide press.